2016
DOI: 10.3846/btp.17.11130
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of corporate social responsibility introduction in small and medium-sized enterprises: a systematic review of the literature

Abstract: Corporate social responsibility is considered as an important part of entrepreneur's strategic behaviour. Its purpose is not only to achieve and maintain the good economic results,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is generally understood that entrepreneurs can lead and show direction through RL because personal values and ethical motives impact their choices (Burton & Goldsby, 2009). The planned activities identified in this study are likely to result in the expected benefits of SR, as suggested by Hodindova and Sadovský (2016): enhancing trust and employee motivation, achieving a greater degree of transparency, improving reputation and employer-employee and supplier-client relations, increasing attractiveness for quality employees and strengthening employee loyalty. However, the novelty of this study was the expressed desire to create impact and give back to the community.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…It is generally understood that entrepreneurs can lead and show direction through RL because personal values and ethical motives impact their choices (Burton & Goldsby, 2009). The planned activities identified in this study are likely to result in the expected benefits of SR, as suggested by Hodindova and Sadovský (2016): enhancing trust and employee motivation, achieving a greater degree of transparency, improving reputation and employer-employee and supplier-client relations, increasing attractiveness for quality employees and strengthening employee loyalty. However, the novelty of this study was the expressed desire to create impact and give back to the community.…”
Section: Discussionmentioning
confidence: 85%
“…A clearer understanding of how entrepreneurs perceive CSR might reveal how motivations other than short-term economic influence their decision-making (Klein & Kellermanns, 2008) and leadership. One element of the broad CSR concept is SR, which is suggested to provide enhanced trust and employee motivation, a greater degree of transparency, an improved reputation, improved employer–employee and supplier–client relations, increased attractiveness to quality employees and strengthened employee loyalty (Hodindova & Sadovský, 2016). The reasons for engaging in SR have been suggested to range from purely ethical ones to purely instrumental ones (Garriga & Melé, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The fulfilment of the third condition presupposes interactions between the elements, because for the purpose of achieving a common objective in the system they are positioned in terms of each other in a certain order, i.e. they form a structure (Strakova, 2015;Armas-Cruz et al, 2017;Hashem-Nazari et al, 2017;Hodinkova & Sadovsky, 2016;Wegner et al, 2017;Dobrovic & Timkova, 2017).…”
Section: Introductionmentioning
confidence: 99%